PERAN KOMUNIKASI PEER GROUP ONLINE DAN KONSEP DIRI: Studi Etnografi Virtual pada Followers Akun Twitter @thestorykids - Nadyna Andharu Wisaksana, (2022)
The number of members in a group posolutely makes us have to adapt in order to communicate with other people in the group. Even though there are same interests, hobbies, and goals, it can not be denied that there will be differences of opinion and ways of communicating. Communication that occurs within the group can affect each individual, gain satisfaction, take on roles, and the existence of linkages between fellow group members. The more often we communicate in the group, the habits that exist will certainly be carried away by us, we will follow the things that are done by the members of the group unconsciously, then we will get used to it slowly. A group of Stray Kids' fans in Indonesia, Indonesian STAY, on Twitter looks like they rarely started the war with other groups of fans, they also know it's better not to interact with hate speech on social media. The purpose of this research is to determine the role of the STAY Indonesia online community in forming the self-concept of it's members. This research is structured using virtual ethnographic study methods and social exchange theory. The interview with 5 (five) informants led to a result that communication and interaction experiences about life between the members of Indonesian STAY made their behavior get better, such as caring for people who need help because Indonesian STAY often shows concern for each other and to the environment.